Phenology of Colorado alpine plants - Holway, James Gary, author; Ward, Richard T., advisor; Salisbury, Frank B., committee member; Parke, Robert V., committee member; Lechleitner, Robert R., committee member (Colorado State University. Libraries, 1962)
During the summers of 1960 and 1961 a study of the phenology of alpine angiosperms was conducted in the vicinity of False Mummy Pass, Rocky Mountain National Park, Colorado. Ten primary phenology study stations were selected in 1960, representing variations in slope, exposure, altitude, snow cover and composition of the vegetation. In 1961 two more stations were added, one to study the effects of the artificial application of melt-water to the vegetation, and the other to study the effects of progressively later lying snow on phenology and vegetational composition. Semi-permanent quadrats 25 by 25 cm were established at each station to facilitate relocation of individual plants and clones. An average of slightly over eight species per quadrat was observed weekly for phenological change from early June to late September. The vegetation was sampled for frequency and cover at all stations except one, a heterogeneous area of willow scrub. The frequency and cover data for the primary phenology stations were applied to the Kulczinski Index of Association to determine station affinities. Environmental data, including air temperature, relative humidity, wind velocity, soil temperature, and soil moisture, were recorded at each station. The average depth of soil at each station was also determined by use of a soil coring tool. The growing season could arbitrarily be divided into four rather distinct periods of flowering. The analysis of data showed no consistent phenological patterns which could be associated with exposure, slope or elevational differences. There were, however, consistent patterns noted with dry, exposed stations and with the wetter, snow accumulation stations. It was concluded that the differences in the broad phenological patterns of dry and wet stations are primarily related to two basic factors. First, that covering of snow into mid-June in the snow accumulation station delays the arrival of appropriate environmental conditions, thereby delaying vegetative activity. Second, and probably most important, the differences in microenvironment in the wet sites apparently selects different species with dissimilar phenologic response patterns. Attempts to correlate weather data to phenology were generally unsuccessful. However, it was suggested that temperature responses will probably be found to be most important in the alpine. The maximum growing season was estimated to be 14 to 15 weeks at the dry stations, and the minimum 5 to 6 weeks in the center of a snow basin. The data indicate that the majority of species required a period of 5 to 11 weeks to develop from the resumption of vegetative activity in the spring to seed dispersal. Many species were observed to rebloom near the end of the growing season. The possible causes include a delay of an existing bud, production of a new bud resulting from excess carbohydrate production, and bolting of a floral bud primordium produced in a perennating bud. The production of new, reduced leaves near the end of the growing season was also observed in several species. These leaves apparently overwinter without harm, and allow the species to respond more quickly in the spring. There were fewer total flowers produced in the area in 1961. The possible causes were discussed, including the probable importance of carbohydrate accumulation and build up for abundant flowering. Suggestions for future research were made. A selection of a limited number of the more important species which could be examined more frequently over a wider variety of habitats, and in more than one major study area would provide more specific information on phenologicaresponses. Further, the need for detailed studies concerning the pollination, growth characteristics, and ecotypic potentials of alpine species was emphasized.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Mountain plants -- Colorado